FACTORS DETERMINING THE DECISION TO USE SHARIA FINANCIAL PRODUCTS IN THE DIGITAL ERA - Febriyanthi, Hesty; Wati, Lela Nurlaela; Soma, Abdul Mukti (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
This study examines the impact of Islamic financial literacy, sharia compliance, returns, customer risk profiles, digitalization and social factors, and religiosity on the decision to use Islamic financial products in Islamic banking. This study employed a quantitative methodology, including a sample of 302 productive-age respondents with bank accounts in DKI Jakarta. Data analysis was conducted using multiple regression with SmartPLS. The results show that Islamic financial literacy, customer risk profiles, digitalization and social factors, and religiosity have a positive influence on the decision to use Islamic financial products. Conversely, sharia compliance and returns do not have a significant effect. These findings theoretically enhance the literature on consumer behavior and Islamic finance by illustrating that value-based elements, especially religiosity, exert a more significant influence than economic concerns in the decision to utilize Islamic financial products. The research findings suggest that Islamic banking, regulators, educational institutions, and religious organizations should collaborate to enhance Islamic financial literacy programs, expedite the transition to digital services, and formulate marketing strategies that highlight Islamic values and religiosity to promote the adoption of Islamic financial products. This study develops a model that includes financial, behavioral, technological, and religiosity characteristics to elucidate the decision to utilize Islamic financial products, contrasting with previous research that predominantly emphasized economic considerations. This study illustrates that religiosity exerts a more significant impact than financial returns and views of Islamic compliance, offering a novel viewpoint on value-driven decision-making within the Islamic banking sector.